ANALISIS RASIO KEUANGAN UNTUK MENGUKUR TINGKAT KESEHATAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Ice Mutiara; Effendi, Syahril (LPPM Universitas Putera Batam, 2021)
This study aims to analyze the effect of Profitability, Liquidity, Leverage, Operating Capacity, and Sales Growth on the Company Health Level. The population in this study consisted of 13 automotive and component subsector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique in this study used purposive sampling and 9 companies meet the sample selection criteria. The data are in the form of data figures obtained from the annual financial statements of the automotive and components subsector. The data collected in this study were analyzed using the SPSS application version 25. The method of analysis in this study is a descriptive statistical analysis, classical assumption tests, multiple linear regression test, and hypothesis testing consisting of a t-test, F test, and coefficient of determination test. The results show that partially Profitability, Liquidity, and Operating Capacity had a positive and significant effect on the Company Health Level. Meanwhile, Leverage and sales growth have no significant and negative effect on the Company Health Level. Simultaneously, it shows that Profitability, Liquidity, Leverage, Operating Capacity, and Sales Growth have a positive effect on the Company Health Level.